2012
DOI: 10.1038/nrd3625
|View full text |Cite
|
Sign up to set email alerts
|

RNA therapeutics: beyond RNA interference and antisense oligonucleotides

Abstract: Here we discuss three RNA therapeutic technologies exploiting various oligonucleotides that bind RNA by base-pairing in a sequence-specific manner yet have different mechanisms of action and effects. RNA interference and antisense oligonucleotides downregulate gene expression by enzyme-dependent degradation of targeted mRNA. Steric blocking oligonucleotides block access of cellular machinery to pre-mRNA and mRNA without degrading the RNA. Through this mechanism, blocking oligonucleotides can redirect alternati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

6
828
0
15

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 1,023 publications
(881 citation statements)
references
References 103 publications
6
828
0
15
Order By: Relevance
“…Eteplirsen‐induced skipping of exon 51 restores the mRNA reading frame, allowing production of an internally deleted but functional dystrophin protein. This is supported by the finding that internally deleted dystrophin proteins occur in patients with Becker muscular dystrophy, a dystrophinopathy allelic to DMD, but with a less severe phenotype 9. The ability of eteplirsen to induce expression of dystrophin in DMD patients was demonstrated by an observed increase of dystrophin‐positive fibers in skeletal muscle, observed increases in dystrophin intensity in this1 and other studies,10, 11 and by the observed restoration of the dystroglycan complex, as evidenced by localization of neuronal nitric oxide synthase and B‐dystroglycan to the sarcolemma 12…”
mentioning
confidence: 79%
“…Eteplirsen‐induced skipping of exon 51 restores the mRNA reading frame, allowing production of an internally deleted but functional dystrophin protein. This is supported by the finding that internally deleted dystrophin proteins occur in patients with Becker muscular dystrophy, a dystrophinopathy allelic to DMD, but with a less severe phenotype 9. The ability of eteplirsen to induce expression of dystrophin in DMD patients was demonstrated by an observed increase of dystrophin‐positive fibers in skeletal muscle, observed increases in dystrophin intensity in this1 and other studies,10, 11 and by the observed restoration of the dystroglycan complex, as evidenced by localization of neuronal nitric oxide synthase and B‐dystroglycan to the sarcolemma 12…”
mentioning
confidence: 79%
“…The application of siRNAs, designed to block the expression of disease-related proteins, has therefore emerged as a promising therapeutic strategy for the treatment of various diseases [1][2][3]. Pulmonary disorders, including chronic obstructive pulmonary disease (COPD) and lower respiratory infections, are currently amongst the top ten causes of death worldwide [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…The target gene is typically one that is overexpressed in a specific disease (cancer, cardiovascular, or metabolic), and its knock-down allows the diseased tissue to resume its normal function. 2,3 Despite its relatively recent discovery, the simplicity and efficiency of the RNA interference process have led to the rapid proliferation of oligonucleotide-based drug candidates, and several clinical trials have been conducted to evaluate their feasibility for use as therapeutics. However, only two antisense oligonucleotide drugs have made it through the pipeline: Fomivirsen (Vitravene) and Mipomersen (Kynamro) were approved in 1998 and 2013, respectively.…”
Section: ■ Introductionmentioning
confidence: 99%